2016
DOI: 10.4314/ecajs.v21i2.12
|View full text |Cite
|
Sign up to set email alerts
|

An audit of the quality of surgical operation notes in a Nigerian teaching hospital

Abstract: Background: Operation note records are important tools for ensuring patients' continuity of care, for research purposes and medico-legal reasons. They can effectively serve these purposes only if well documented. The main objective of this study was to assess the practice of recording the operation notes among surgical trainees in a Nigerian Teaching Hospital. Methods: Operation notes completed by doctors in the Surgery Department over a 2-month period were audited for completeness, legibility and conformity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
3
1
Order By: Relevance
“…In this study, the type of anesthesia and intraoperative findings were documented in more than 90% of the notes that we investigated, and this was comparable with previous studies 26 . Position of the patient, type of incision, operative diagnosis, and closure technique were less frequently documented, which was lower than the rates observed in the previously mentioned studies conducted in Nigeria (82%) 25 and comparable with the study conducted in Pakistan (69%) 24 , but higher than the proportion observed in the study carried out in Sudan (26.9%) 20 .…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In this study, the type of anesthesia and intraoperative findings were documented in more than 90% of the notes that we investigated, and this was comparable with previous studies 26 . Position of the patient, type of incision, operative diagnosis, and closure technique were less frequently documented, which was lower than the rates observed in the previously mentioned studies conducted in Nigeria (82%) 25 and comparable with the study conducted in Pakistan (69%) 24 , but higher than the proportion observed in the study carried out in Sudan (26.9%) 20 .…”
Section: Discussioncontrasting
confidence: 63%
“…RCSE guidelines stipulate that both date and time should be recorded in operation notes; this was consistently documented at the hospital under study. Contrary to this, the time of surgery was commonly omitted in operation notes evaluated by investigators in Nigeria and Pakistan 24 , 25 ; however, a study conducted in Sudan found that the time was documented in 81% of notes 20 .…”
Section: Discussionmentioning
confidence: 99%
“…This may give room for errors/omissions in the notes especially in situations where the notes are written, unsupervised, by assistants who may not have clearly grasped the 3,5 operative procedure. Other studies from Nigeria showed that senior registrars are the main writers of [11][12][13][14] operation notes in all the centers. This was irrespective of whether they were the operating surgeons or not.…”
Section: Characteristics Of the Sampled Populationmentioning
confidence: 99%
“…The feedback from this study should therefore help in formative assessment and education from the self-mirroring effect. There are studies from Nigeria on the audit of operation notes [11][12][13][14] writing in tertiary centers. The authors have not however seen any assessment based solely on trainees self assessment.…”
Section: Introductionmentioning
confidence: 99%